2022
DOI: 10.21608/ejhm.2022.262194
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Single Anastomosis Sleeve-Jejunal Bypass vs Laparoscopic Mini-Gastric Bypass in Morbid Obese Patients and Resolution of Diabetes Mellitus, A Single Centre Experience

Abstract: Background: The most effective therapy for morbid obese patients now available is bariatric surgery, which can help patients losing weight effectively and sustainably while also improving their quality of life and comorbidities associated with obesity. Worldwide, the one anastomosis gastric bypass (OAGB) technique is one of the most performed bariatric surgeries. Objective: The study's objective was to compare the outcomes of the OAGB, with those of the single anastomosis sleeve jejunal bypass (SASJ) as a new … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(14 citation statements)
references
References 16 publications
(28 reference statements)
0
0
0
Order By: Relevance
“…Three studies were non-randomized clinical trials [ 24 , 28 , 29 ], two studies were randomized clinical trials [ 25 , 26 ], three studies were retrospective cohorts [ 18 , 27 , 30 ], and one study was a prospective cohort [ 19 ]. The studies were conducted in Iran [ 24 , 27 , 30 ] and Egypt [ 18 , 19 , 25 , 26 , 28 , 29 ]. Patients were mostly females, with males representing only 14-34.9% of the sample size.…”
Section: Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…Three studies were non-randomized clinical trials [ 24 , 28 , 29 ], two studies were randomized clinical trials [ 25 , 26 ], three studies were retrospective cohorts [ 18 , 27 , 30 ], and one study was a prospective cohort [ 19 ]. The studies were conducted in Iran [ 24 , 27 , 30 ] and Egypt [ 18 , 19 , 25 , 26 , 28 , 29 ]. Patients were mostly females, with males representing only 14-34.9% of the sample size.…”
Section: Reviewmentioning
confidence: 99%
“…Moreover, most studies did not report whether the sample size was calculated before commencing the study. The two randomized controlled trials [ 25 , 26 ] showed high ROB regarding the deviations from intended interventions as no information was provided on whether carers were aware of the assigned interventions. Furthermore, ROB was high regarding missing outcome data as we could not ascertain whether data were provided for all randomized patients.…”
Section: Reviewmentioning
confidence: 99%
See 3 more Smart Citations